(untitled) (Research, Society and Development, 2023)
Knowing that ticks have bioactive molecules in their saliva which modulate hemostatic and immunomodulatory activities in humans, we carried out a systematic search for biomolecules present in tick saliva with great pharmacological potential. We evaluated studies published in the last ten years. Following the recommendations of the Prisma tool, primary and secondary studies of a systematic nature were selected, with no language or country restriction. Studies that included arthropods other than ticks and studies in which the use of saliva had no pharmacological application were excluded. For searches, we used the following databases: MEDLINE®/PubMed®, Web of Science, LILACS, EMBASE, Cochrane and SCOPUS. The methodological quality was performed using the tools available in Joanna Briggs, always with two or more independent evaluators. The generated data were tabulated and summarized through qualitative narrative analysis. The methodology selected 19 articles that met the eligibility criteria. The saliva of hard ticks, found in the Americas, is more promising when used in experimental studies with human cells. The elucidation of the biomolecules was possible, with evasin and serpine being the biomolecules with the most evident pharmacological potential for anti-inflammatory action. In the selected studies, we found only experimental studies, with no pre-clinical or clinical studies, making methodological qualification difficult; in some studies, with the biomolecule Evasin and Serpin, the need for elucidation of these biomolecules in question was suggested. Thus, we found evidence that the saliva of American hard ticks is the most studied for pharmacological applications of anti-inflammatory and immunomodulatory action.